PENGARUH LATIHAN PIRAMIDA DESCENDING DENGAN IRAMA LAMBAT DAN CEPAT TERHADAP KEKUATAN, KECEPATAN, DAYA LEDAK DAN HYPERTROPY OTOT TUNGKAI - Hartoto, Setyo (Journal of Sport Science and Education, 2017)
Related to weight training with pyramid system, in this research the researcher will focus on ascending and descending pyramid system, comparison of multiple set training with pyramid model will be done with fast and slow rhythm, rhythm comparison and pyramid drill model which will be used to know the mprovementand comparison of increased strength, speed, explosive power and hypertrophy of the leg muscles. This type of research is a quasi-experimental research, using the design of "The Randomized Group Pretest-postest Design". Treatment was done for 8 weeks (two months) with exercise frequency 3 times per week. Thesample was divided into 2 groups, group 1 was given a descending pyramid training using fast rhythm, group 2 was given a descending pyramid training using a slow rhythm. It is a significant influence of the descending pyramid load system with fast and slow rhythm to strength, speed and hypertrophy of the legmuscles, but not significant in explosive power for the slow rhythm descending pyramid load.